Rancang Bangun Modul Praktikum Penyearah Satu Fasa Terkendali - Marhatang Marhatang; Remigius Tandioga; Muhammad Ruswandi Djalal; Andi Muh. Ilham; Rifa Dwia Ayanis (Universitas Darul Ulum, 2022)
The Industrial Electronics Practicum is an advanced learning process complementing theoretical knowledge and is mandatory for every student in the Energy Conversion Engineering (TKE) Study Program at Ujung Pandang State Polytechnic (PNUP). Nevertheless, its implementation is often suboptimal due to the lack of practicum modules available in the TKE Laboratory. To address this issue, this research aims to design and create a practicum module for a controlled single-phase rectifier, filling the gap in the TKE Laboratory's offerings. The design carried out in this research begins with thyristor selection, control circuit design, mechanical design, and power circuit design. After the design is carried out, it continues with manufacturing and assembly, tool testing, and data analysis. In the practical module testing, this controlled single-phase rectifier uses half waves, with a resistive load (R). The test results of the module that has been created show that this practical module can operate well and produce an output waveform that can be said to be in accordance with theory.